Strategies for enhancing fire performance of steel bridges. (15th January 2017) - Kodur, Venkatesh K.; Aziz, Esam M.; Naser, Mohannad Z.
Highlights: A systematic approach for overcoming fire hazard in bridges is developed. The proposed approach for assessing vulnerability of a bridge to fire is validated. Steps for undertaking fire resistance analysis of bridges is presented. Relevant design strategies for mitigating fire hazard in bridges is discussed. Abstract: This paper presents an approach for developing strategies to mitigate fire hazard in critical bridges. The proposed approach comprises of two steps; namely estimating fire risk in a bridge, and then developing strategies for minimizing fire hazard on a critical bridge. As part of the first step, an analytical procedure is employed to derive a fire-based importance factor to assess the vulnerability of a bridge to fire. When the bridge is susceptible to likely fire damage, the second step involves a sequential finite element analysis to develop alternate strategies for minimizing the consequences of fire hazard on that bridge. The applicability of this approach is demonstrated through case studies on three major steel bridges that experienced failure due to fire incidents in recent years. It is shown that the proposed approach can be used as a practical tool for identifying critical bridges from the point of fire hazard and then developing solutions to overcome fire hazard in such critical bridges.